Surface-reconstructed manganese oxides for enhanced external-oxidant-free degradation of bisphenol A: A direct electron transfer mechanism - Dawei Wang; Yihan Zhu; Keyi Gao; Zhuang Liu; Tong Li; Lin Chen; Yilan Jiang (Chemical Engineering Journal, 2026)

Spatiotemporal Characteristics and Driving Mechanisms of Non‐Extreme Precipitation Variability Over Mainland China - Yue Sun; Baofu Li; Keyi Tong; Dong Cui; Kairong Shi; Haijun Liu (International Journal of Climatology, 2026)
Against the background of global warming, non‐extreme precipitation is an important component of the regional moisture background and the normal hydrological cycle, yet its variability remains insufficiently understood. Based on daily CHM_PRE V2 precipitation for 1961–2024, ERA5 reanalysis, and outputs from 14 CMIP6 models, this study systematically investigates the spatiotemporal characteristics of non‐extreme precipitation variability over mainland China, its projected responses under 1.5°C and 2.0°C global warming levels, and its driving mechanisms. The results show that non‐extreme precipitation variability exhibits pronounced regional contrasts and strong timescale dependence, with the eastern monsoon region showing the largest variability, the arid northwest and the Tibetan Plateau exhibiting lower variability, and the intraseasonal scale displaying the strongest response. Under future warming, non‐extreme precipitation variability generally increases, but with marked regional differences: it decreases in the eastern monsoon region but increases in northwestern China and over the Tibetan Plateau, and the magnitude of change is larger at 2.0°C than at 1.5°C. A thermodynamic–dynamic decomposition of projected 850‐hPa moisture flux convergence under the 1.5°C warming level further shows that the regional mechanisms are highly heterogeneous: dynamic circulation adjustment dominates the moisture flux convergence (MFC) response in the eastern monsoon region and the arid northwest, whereas thermodynamic moistening dominates over the Tibetan Plateau. Thermodynamic background factors exert some influence, but their explanatory power is limited. In contrast, large‐scale circulation exerts clearer seasonal and regional controls. In particular, summer non‐extreme precipitation variability in eastern China is closely linked to the western Pacific subtropical high, and the associated enhancement of low‐level MFC is primarily dominated by anomalous circulation rather than by the direct thermodynamic contribution of increased specific humidity. Overall, non‐extreme precipitation variability over mainland China arises from the combined effects of regional thermodynamic background differences and seasonal reorganisation of large‐scale circulation.

Molecular-weight-dependent effects of humic acid on hexavalent chromium accumulation and reduction in green microalgae - Li Luo; Keyi Zhou; Mawuli Dzakpasu; Kena Zhang; Tong Yang; Wenshan Guo; Huu Hao Ngo; Xiaochang C. Wang (Journal of Hazardous Materials, 2026)

Naked mole-rat-derived high molecular weight hyaluronic acid protects against DSS-induced intestinal inflammation - Shuyin Wu; Lei Xing; Xiaolong Wu; Run Quan; Keyi Du; Jianchun Han; Huili Tong; Shuai Shi (Food Bioscience, 2025)

The spatial-temporal pattern of RMT network stability in the estuarine phytoplankton community - Mingliang Zhou; Yan Xu; Keyi Zhu; Tong Teng; Xumeng Huo; Xinyue Chen; Weili Hou; Jiaqiang Liu; Shengjun Yan; Imran Khan (Journal of Environmental Management, 2025)

Enterovibrio qingdaonensis sp. nov. and Enterovibrio gelatinilyticus sp. nov., two marine bacteria isolated from surface seawater of Qingdao offshore - Keyi Huang; Yi Liu; Yan Wang; Pingping Zhang; Haojin Cheng; Jinfeng Wang; Wanjia Tong; Wang Xiaolei; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2025)